Nanostructured Polymeric, Liposomal and Other Materials to Control the Drug Delivery for Cardiovascular Diseases - Dimitrios Skourtis; Dimitra Stavroulaki; Varvara Athanasiou; Panagiota G. Fragouli; Hermis Iatrou (MDPI AG, 2020)
Cardiovascular diseases (CVDs) are the leading cause of death globally, taking an estimated 17.9 million lives each year, representing one third of global mortality. As existing therapies still have limited success, due to the inability to control the biodistribution of the currently approved drugs, the quality of life of these patients is modest. The advent of nanomedicine has brought new insights in innovative treatment strategies. For this reason, several novel nanotechnologies have been developed for both targeted and prolonged delivery of therapeutics to the cardiovascular system tο minimize side effects. In this regard, nanoparticles made of natural and/or synthetic nanomaterials, like liposomes, polymers or inorganic materials, are emerging alternatives for the encapsulation of already approved drugs to control their delivery in a targeted way. Therefore, nanomedicine has attracted the attention of the scientific community as a potential platform to deliver therapeutics to the injured heart. In this review, we discuss the current types of biomaterials that have been investigated as potential therapeutic interventions for CVDs as they open up a host of possibilities for more targeted and effective therapies, as well as minimally invasive treatments.